Potential vestibular pathway impairment in children with recurrent vertigo: An investigation through air-conducted sound and galvanic vestibular stimulation-triggered vestibular evoked myogenic potentials - Sun, Xiayu; Gao, Dekun; Shen, Jiali; Zhu, Qi; Wang, Lu; Ma, Xiaobao; Wang, Wei; Chen, Xiangping; Zhang, Qing; Jin, Yulian; Chen, Jianyong; Yang, Jun (Frontiers in Neurology, 2022)
Objective: This study was to investigate the potential vestibular pathway impairment through vestibular evoked myogenic potentials (VEMPs), and to explore the pathophysiological significance of these instrument-based findings in children with recurrent vertigo. Materials and Methods: The clinical data of 21 children (mean age 4.67±1.39 years) diagnosed as RVC who met the inclusion criteria of the Bárány Society and 29 healthy children (mean age 4.83±1.34 years) enrolled as control group from February 2021 to December 2021 were collected and analyzed retrospectively. All subjects underwent both cervical VEMP (cVEMP) and ocular VEMP (oVEMP) triggered by air-conducted sound (ACS) and galvanic vestibular stimulation (GVS), respectively. The elicit rate, latency and amplitude asymmetry ratio (AAR) of ACS-cVEMP, ACS-oVEMP, GVS-cVEMP and GVS-oVEMP were analyzed. Results: (1) The elicit rates of ACS-cVEMP and ACS-oVEMP were similar in the two groups (P > 0.05), as well as GVS-cVEMP and GVS-oVEMP (P > 0.05). (2) P1 and N1 latencies of ACS-cVEMP and GVS- cVEMP in the RVC group were longer than those in the control group (P < 0.05). (3) N1 latency of ACS-oVEMP in the RVC group was shorter than that in the control group (P < 0.05), while there was no significant difference in P1 latency of ACS-oVEMP (P > 0.05). The N1 and P1 latencies of GVS-oVEMP were not significantly different (P > 0.05). (4) There was no statistical difference in the AAR of ACS-cVEMP and GVS-cVEMP. Although there was an increased AAR of ACS-oVEMP in the RVC group (P < 0.05), AAR was within the normal range. However, no statistical difference was found in AAR of GVS-oVEMP in the two groups (P > 0.05). Conclusion: The latencies of ACS-cVEMP and GVS-cVEMP in children with recurrent vertigo were significantly prolonged compared with those in healthy children and there was no difference in elicit rates of ACS-cVEMP and GVS-cVEMP, suggesting that there might be potential impairment in the inferior vestibular nerve and the subsequent nerve conduction pathway in RVC.